Prospective content in the friendship conversations of young adults. (10th November 2016) - Young, Richard A.; Marshall, Sheila K.; Murray, John
ABSTRACT: Prospection is cognitive processes that involve constructing, encoding, and remembering the future. Less is known about the how these processes are evident in the prospective content of conversations. This study sought to identify and describe evidence of the prospective content in the conversations of friends as they transition to adulthood. The present secondary content analysis of the videotaped conversations of 15 young adult friendship dyads (n = 30, 16 females, 14 males, mean age = 21.3 years) in Canada examined these conversations based the following characteristics of prospection: simulation, reasoning about counterfactuals, constructing multiple possible futures, and episodic memory of the past. Four categories of prospective content were evident in these conversations, these processes were used sparingly in all but one conversation, and relatively few of them were collaborative in that dyad partners did not appear to serve to augment, clarify, or disconfirm prospective content.